Pertimbangan Aspek Sosial Budaya dan Kearifan Lokal dalam Pengembangan Kawasan Danau Tempe Provinsi Sulawesi Selatan - Fadhil Surur; Santun R P Sitorus; Ivanovich Agusta (TATALOKA, 2014)
One of the potential regions in South Sulawesi Province is Tempe Lake region. The socio-cultural conditions of the local community can be an interesting matter to become a foundation in the regional development. The purpose of this study was to identify and to describe the form of community local wisdom in Tempe Lake region that can be considered in the regional development, to analyze the agricultural commodity that become the leading commodity, to identify the development level of rural, to analyze the contents of spatial plan policies that support the local wisdom aspects and to arrange Tempe Lake region’s development referrals with regard to local wisdom. The results showed that 7 local communities has a potential regarding local wisdom aspects. Commodities of fisheries and animal husbandry as leading commodities. Most of the rural areas in Tempe Lake region was at a low level of development. In the RTRW of Sidrap, Soppeng and Wajo Regency had found that assimilation element was the most heavily contented element in the three documents. The referrals of Tempe Lake region development with regard to local wisdom could be based on the local knowledge in regional development planning, natural resource management, local economic development, traditional settlements development, cultural village development, and protection of cultural sites.